Questioning Schenkerism - Edlund, Bengt (2015)
During the past fifty years Schenkerian theory has been adopted as the main method for analysing tonal music. This book questions the value of Schenker's «tonal analysis» for musical description and interpretation, and discusses its relations to «generative» theory and «implicational» analysis - taking into account its links with linguistic syntax and the perception of tonal closure. It is observed how auxiliary theoretical concepts transform the music so as to pave the way for preordained tonal structures. Alternative readings of the music examples are provided.